2022
DOI: 10.1371/journal.pone.0272501
|View full text |Cite
|
Sign up to set email alerts
|

Which communication technology is effective for promoting reproductive health? Television, radio, and mobile phones in sub-Saharan Africa

Abstract: The use of radio and television as means to spread reproductive health awareness in Sub-Saharan Africa has been extensive, and its impacts significant. More recently, other means of communication, such as mobile phones, have received the attention of researchers and policy makers as health communication tools. However, evidence on which of the two types of communication (i.e. passive communication from TV/radio, or active communication through phones) is more effective in fostering better reproductive health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…However, the refugees who atleast completed primary level education were more likely to use FP. This concurs with several studies [ 31 33 ] which showed that education has the greatest influence on FP use because of knowledge, empowerment, economic status and autonomy hence increased ability to maintain FP method. This demonstrates the fact that low educational level or no education is associated with less empowerment to make own decision but rather rely on a husband or believing on cultural norms.…”
Section: Discussionsupporting
confidence: 92%
“…However, the refugees who atleast completed primary level education were more likely to use FP. This concurs with several studies [ 31 33 ] which showed that education has the greatest influence on FP use because of knowledge, empowerment, economic status and autonomy hence increased ability to maintain FP method. This demonstrates the fact that low educational level or no education is associated with less empowerment to make own decision but rather rely on a husband or believing on cultural norms.…”
Section: Discussionsupporting
confidence: 92%
“…A similar finding was reported in a previous study in Ethiopia [ 43 ]. The importance of radio in promoting sexual and reproductive health education and practices in SSA has been highlighted in several studies [ 43 , 49 , 50 ]. Local radio stations in SSA commonly engage resource persons to educate the public on important health matters such as contraception [ 51 ], which could improve women’s ability to access quality contraceptive counselling.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Rwanda showed that mothers were the group that had the most significant influence on the decision of pregnant women to seek care [ 117 ]. In Africa, mobile phones are displacing radio and television as a means of social communication [ 118 ]. Mass media and educational interventions based on SMS and voice message reminders should be used to increase pregnant women’s prenatal visits [ 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%